Transcription readthrough is prevalent in healthy human tissues and associated with inherent genomic features - Caldas, Paulo (2024)
We thank João Neto, Silvia Carvalho, and the remaining Computational Multi-Omics Lab members at UCIBIO for their helpful comments and suggestions. Paulo Caldas was a recipient of a Marie Skłodowska-Curie Postdoctoral Fellowship (FOX-MTN-HORIZON-MSCA - 2021-PF-01-01). This work was financed by national funds from Fundação para a Ciência e Tecnologia (FCT), in the scope of the projects UIDP/04378/2020 and UIDB/04378/2020 of the Research Unit on Applied Molecular Biosciences (UCIBIO) and the project LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy - i4HB. The Genotype-Tissue Expression (GTEx) Project was supported by the Common Fund of the Office of the Director of the National Institutes of Health and by NCI, NHGRI, NHLBI, NIDA, NIMH, and NINDS. Publisher Copyright: © 2024, The Author(s).